Dilepton Production in Transport-based Approaches. (April 2015) - Weil, Janus; Endres, Stephan; van Hees, Hendrik; Bleicher, Marcus; Mosel, Ulrich
Abstract: We investigate dilepton production in transport-based approaches and show that the baryon couplings of the ρ meson represent the most important ingredient for understanding the measured dilepton spectra. At SIS energies, the baryon resonances naturally play a major role and affect already the vacuum spectra via Dalitz-like contributions, which can be captured well in transport simulations. Recent pion-beam measurements at GSI will help to constrain the properties of the involved resonances further.